Levels and correlates of involuntary childlessness among married women aged 45-49 in Mozambique - Mabe, Masego (My University, 2021)
Background: involuntary childlessness due to infertility in Mozambique has social, psychological and health consequences for couples. Mozambique has one of the highest infertility prevalence in sub-Saharan Africa. However, there are very few studies that exist in Mozambique which indicate the level and correlates of childlessness and infertility in the country. Objectives: The current study aims to examine the level and correlates of childlessness among married women ages 45-49 in Mozambique so as to address the existing gap in research on the real burden of childlessness in the country. Method: The study analysed the 2015 Mozambique Demographic and Health Survey data to examine the levels and correlates of infertility among a sample of 363 married women aged 45-49. The study implemented a cross-sectional study design. Descriptive statistics in the form of tables and graphs are provided to describe the characteristics of the study sample. Binary logistic regression was implemented to indicate the relationship between the binary categorised variable childlessness and predictor variables. Findings: A total of 4.14% of married women in Mozambique were found to be childless. Most of these women reside in the Northern region. Majority of childless women reside in the rural areas. The higher the level of education, the higher the likelihood that a woman was childless (OR: 2.25). The odds of childlessness were higher for women that were employed compared to those that were unemployed (OR: 1.6). Remarriage, having tested for HIV and age at first cohabitation were some of the factors positively associated with the likelihood of childlessness amongst married women. The latter therefore contributed to whether a woman was childless or not. Conclusion: there are a significant number of childless married women in Mozambique between ages 45-49. The odds of childlessness increased by level of education and type of place of residence with the odds increasing for women residing in rural areas. Government needs to implement educational programs on the possible causes, prevention and treatment of infertility in the country to cater for women battling with infertility issues
A research report submitted in partial fulfilment for the degree of Master of Arts (in Health Demography), to the Faculty of Humanities, at the University of the Witwatersrand, 2021